The p75 Neurotrophin Receptor Promotes Amyloid-β(1-42)-Induced Neuritic Dystrophy In Vitro and In Vivo - Knowles, Juliet K. (Society for Neuroscience, 2009)
Oligomeric forms of amyloid-β (Aβ) are thought to play a causal role in Alzheimer's disease (AD), and the p75 neurotrophin receptor (p75(NTR)) has been implicated in Aβ-induced neurodegeneration. To further define the functions of p75(NTR) in AD, we examined the interaction of oligomeric Aβ(1-42) with p75(NTR), and the effects of that interaction on neurite integrity in neuron cultures and in a chronic AD mouse model. Atomic force microscopy was used to ascertain the aggregated state of Aβ, and fluorescence resonance energy transfer analysis revealed that Aβ oligomers interact with the extracellular domain of p75(NTR). In vitro studies of Aβ-induced death in neuron cultures isolated from wild-type and p75(NTR−/−) mice, in which the p75(NTR) extracellular domain is deleted, showed reduced sensitivity of mutant cells to Aβ-induced cell death. Interestingly, Aβ-induced neuritic dystrophy and activation of c-Jun, a known mediator of Aβ-induced deleterious signaling, were completely prevented in p75(NTR−/−) neuron cultures. Thy1-hAPP(Lond/Swe) × p75(NTR−/−) mice exhibited significantly diminished hippocampal neuritic dystrophy and complete reversal of basal forebrain cholinergic neurite degeneration relative to those expressing wild-type p75(NTR). Aβ levels were not affected, suggesting that removal of p75(NTR) extracellular domain reduced the ability of excess Aβ to promote neuritic degeneration. These findings indicate that although p75(NTR) likely does not mediate all Aβ effects, it does play a significant role in enabling Aβ-induced neurodegeneration in vitro and in vivo, establishing p75(NTR) as an important therapeutic target for AD.